2020
DOI: 10.1590/s0102-053620200308
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid treatments induce resistance to Tuta absoluta and Tetranychus urticae on tomato plants

Abstract: This study was performed to evaluate the effect of exogenous application of salicylic acid as a resistance inducer to two-spotted spider mite and tomato pinworm on tomato genotypes. Bioassays were carried out in three commercial genotypes (‘Redenção’, ‘Giuliana’, and ‘Alambra’) and one wild genotype (Solanum habrochaites var. hirsutum, accession PI-127826). Average distance travelled by the two-spotted spider mite and number of eggs deposited over the leaflets of the genotypes were investigated. Concerning pin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
2
6
0
1
Order By: Relevance
“…of this phytophage as evidenced byFernandes et al 2009 andSantamaria et al 2020 Similar results of the in uence of AS on the reduction of T. urticae eggs were observed byFavaro et al (2019) when evaluating two strawberry cultivars Aromas and Sweet Charlie, which show a positive correlation between AS doses (25, 50 and 75mg L-1) and the reduction in the number of eggs, however the Sweet Charlie cultivar showed higher decrease in the number of eggs in relation to doses. In tomatoPulga et al (2020) also observed a correlation between AS doses (25, 50 and 75mg L-1) and the reduction in T.urticae oviposition. In the present study, the application of AS may have activated the defense differently in the bean cultivars, since, as observed, only the cultivar Garapiá showed a positive response between the doses of AS and the reduction of oviposition.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…of this phytophage as evidenced byFernandes et al 2009 andSantamaria et al 2020 Similar results of the in uence of AS on the reduction of T. urticae eggs were observed byFavaro et al (2019) when evaluating two strawberry cultivars Aromas and Sweet Charlie, which show a positive correlation between AS doses (25, 50 and 75mg L-1) and the reduction in the number of eggs, however the Sweet Charlie cultivar showed higher decrease in the number of eggs in relation to doses. In tomatoPulga et al (2020) also observed a correlation between AS doses (25, 50 and 75mg L-1) and the reduction in T.urticae oviposition. In the present study, the application of AS may have activated the defense differently in the bean cultivars, since, as observed, only the cultivar Garapiá showed a positive response between the doses of AS and the reduction of oviposition.…”
mentioning
confidence: 59%
“…urticae showed a strong interaction of treatments in both cultivars p-value ≤ 0.0001, thus showing that AS in all its dosages directly affect the amount of oviposition of this phytophagous (Table 1). Some studies with the exogenous application of the phytohormones AS and AJ have shown promising results regarding the reduction of the number of T. urticae eggs in several crops, such as cotton (Omer et al, 2001), beans (Farouk and Osman, 2011) and tomato (Pulga et al, 2020). Still in Table 1, it is observed in the average number of eggs ( ) that the dose that most reduces the amount of eggs was the treatments T5 for Fepagro26 and T7 for Garapiá, however the doses T6 and T7 in both cultivars showed apparent toxicity in the plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in hormone regulation may also induce plants’ anti-herbivore characteristics [ 37 ]. In particular, we found that several genes involved in SA metabolism were induced by the T genotype to T. absoluta and could be involved in the tolerance process [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our ndings are in compliance with previous surveys on invertebrate pests in this regard. For example, foliar application of SA signi cantly inhibited the damage of Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) on cotton (El-Sherbeni et al 2019), Aphis gossypii Glover (Hemiptera: Aphididae) on melon (Moreno-Delafuente et al, 2020), and Tetranychus urticae Koch (Acari: Tetranychidae) on tomato (Pulga et al 2020). In contrast, R 0 , r, and λ were highest when P. citri were fed on control and vermiwash-treated seedlings.…”
Section: Discussionmentioning
confidence: 99%